Real-Time Imaging of Retinal Cell Apoptosis by Confocal Scanning Laser Ophthalmoscopy and Its Role in Glaucoma - Yang, Elizabeth; Al-Mugheiry, Toby S.; Normando, Eduardo M.; Cordeiro, Maria F. (Frontiers in Neurology, 2018)
Glaucoma is one of the leading causes of irreversible blindness in the world. It is characterised by the progressive loss of retinal ganglion cells (RGCs), mainly through the process of apoptosis. Clinically, glaucoma often presents only after significant and irreversible loss of visual function has occurred, therefore, early detection of RGC apoptosis is inordinately important in disease prevention. The novel technology called DARC (Detection of Apoptosing Retinal Cells) allows real time in-vivo quantification of apoptosing cells through the use of a fluorescent biomarker and a confocal scanning ophthalmoscope. A recent Phase I clinical trial has evaluated the safety of DARC and its ability to detect retinal apoptosis in glaucoma patients and healthy volunteers. Results suggest that DARC may have potential in the early detection of glaucoma, which could help alleviate the medical, social and economic burden associated with this blinding condition.